PENGARUH ATMOSFER RESTORAN TERHADAP MINAT BELI KONSUMEN REMAJA DI RESTORAN CEPAT SAJI (STUDI KASUS KFC DAN MC DONALD JIMBARAN) - Ni Luh Suastuti (Jurnal Ilmiah Hospitality Management, 2015)
The rapid growth of tourism development in Jimbaran, South Kuta Badung Bali makes this area is flooded with tourism facilities. One of them is a fast-food restaurant. This is influenced by very high demand of fast food products in the region, especially for teenagers. This is influenced by many factors such as faster, more practice, delicious, more prestigious, more comfortable place, nice atmosphere, and there are still many more other factors. The restaurant atmosphere is one of the five essential product elements in the restaurant business. The purpose of this study was to determine the influence of restaurant atmosphere for teenage consumers consuming at fast food restaurants (case study: KFC and Mc Donald Jimbaran). This study found that the atmosphere of the restaurant significantly influence teenage consumers’ intention to purchase fast food products (KFC and case studies in Jimbaran McDonald). The restaurant atmosphere is at 40.50% effect on teenage consumers’ intention in fast food restaurants, especially KFC and Mc Donald Jimbaran and 59.50% are influenced by other factors which are not examined in this study.